Development of Digital Counseling Media in Preventing Family Disintegration in the Era of Disruption - Wilda Rusydiana Izza; Sayyidah Aida Rahmatika; Diajeng Sabila Aulia Nur Islami, (Proceedings Of International Conference On Islamic Counseling Studies (ICONICS), 2025)
The rapid changes brought about by the era of digital disruption have had a significant impact on the harmony of Muslim families, including an increased risk of conflict, disintegration, and communication challenges between family members. This study aims to design an interactive, applicable, and Islamic value-based digital da'wah-counseling content model as a preventive strategy in family counseling. The approach used is qualitative with a library research method, with data collected from journals, books, scientific articles, and relevant documents on family, Islamic counseling, and digital da'wah. The analysis was conducted through data reduction, theme categorization, theory synthesis, and identification of best practices for content design. The results of the study show that Muslim families face challenges in the form of ineffective communication, a lack of Islamic digital literacy, and the influence of negative digital content. Islamic counselors play a strategic role by providing preventive and educational guidance through digital content, which is presented in a personalized and flexible manner. The content model developed through the WhatsApp channel includes material introduction, mentoring classes, and evaluation and reflection, using text, voice notes, videos, infographics, and interactive quizzes. In conclusion, the development of Islamic value-based digital counseling content is effective in strengthening the spiritual, moral, and family resilience of Muslims. As a result, this model can serve as a practical guide for Islamic counselors to provide preventive and applied support to families in the digital age, while also enhancing Islamic digital literacy and family communication skills.